Dyadic Coping in Patients Undergoing Radiotherapy for Head and Neck Cancer and Their Spouses - Badr, Hoda; Herbert, Krista; Bonnen, Mark D.; Asper, Joshua A.; Wagner, Timothy (Frontiers in Psychology, 2018)
BACKGROUND: Head and neck cancer (HNC) adversely affects the psychological (i.e., depression, anxiety) and marital adjustment of patients and their spouses. Dyadic coping refers to how couples cope with stress. It includes positive actions like sharing practical or emotional concerns (i.e., problem- and emotion-focused stress communication; PFSC, EFSC), and engaging in problem- or emotion-focused actions to support each other (problem- and emotion-focused dyadic coping; PFDC, EFDC). It also includes negative actions like avoidance (negative dyadic coping; NEGDC). In this secondary analysis of a randomized pilot trial of a couple-based dyadic coping intervention called SHARE (Spouses coping with the Head And neck Radiation Experience), we first examined associations between patients’ and spouses’ dyadic coping (and satisfaction with dyadic coping; SATDC) and their own/each other’s psychological and marital adjustment. Next, we examined the effects of SHARE relative to usual medical care (UMC) on patients’ and spouses’ dyadic coping. Finally, we examined whether changes in dyadic coping were associated with changes in patients’ and spouses’ psychological and marital adjustment. METHODS AND MEASURES: Thirty HNC patients (80% men) and their spouses (N=60) completed baseline surveys prior to initiating radiotherapy (RT) and were randomized to SHARE or UMC. One month after RT, they completed follow-up surveys. RESULTS: Baseline multilevel Actor-Partner Interdependence Models revealed significant actor effects of PFSC (effect size r=-.32) and PFDC (r=-.29) on depression. For marital adjustment, significant actor effects were found for PFSC, PFDC, EFDC, and SATDC (p<.05, r = .23 to .38). Actor (r=-.35) and partner effects (r=-.27) for NEGDC were also significant. Moderate to large effect sizes were found in favor of SHARE on PFSC (Cohen’s d=1.14), PFDC (d=.64), NEGDC (d=-.68), and SATDC (d=1.03). Improvements in PFDC were associated with reductions in depression and anxiety (p<.05); and, improvements in SATDC were associated with improvements in anxiety and marital adjustment (p<.05). CONCLUSION: SHARE improved positive and decreased negative dyadic coping for patients and spouses. Increases in positive dyadic coping were also associated with improvements in psychological and marital adjustment. Although findings are preliminary, more research on ways to integrate dyadic coping interventions into oncology supportive care appears warranted.